2007
DOI: 10.1029/2007gl030634
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic dynamics and long‐term evolution of a convectively generated oceanic vortex in the Greenland Sea

Abstract: [1] Nonstationary dynamics, realistic long-term evolution, and influence on local convection characterizing an oceanic vortex similar to those observed in the central Greenland Sea were investigated using in situ data, a hierarchy of numerical models, and an analytical theory. A nonhydrostatic model for the simulation of convective plumes was nested into a regional ocean-ice model forced and initialized by a global, atmosphere/ocean/ice model. In the central Greenland Sea, water masses similar to those observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…[55] Although some model studies recently discussed the formation and evolution processes of the SCVs [e.g., Rubino et al, 2007;Oliver et al, 2008], their scales were prescribed, and what determines their scales (or what are their origins) was unknown. Many similarities mentioned above, including the scale, imply that the anticyclonic eddies are a possible candidate for the origin of the SCVs in weakly stratified polar (subarctic) oceans.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[55] Although some model studies recently discussed the formation and evolution processes of the SCVs [e.g., Rubino et al, 2007;Oliver et al, 2008], their scales were prescribed, and what determines their scales (or what are their origins) was unknown. Many similarities mentioned above, including the scale, imply that the anticyclonic eddies are a possible candidate for the origin of the SCVs in weakly stratified polar (subarctic) oceans.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Oliver et al [2008] pointed to the importance of bottom topography as well as background hydrography to interpret the observed behaviors of SCVs. Rubino et al [2007] discussed the longevity of the SCVs in the Greenland Sea, based on the nested model experiments driven by realistic forcings. In these studies, however, the model settings of a homogeneous dense water patch (cylinder) preloaded in the stratified ocean are not sufficient to discuss the origins of SCVs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews of the classic adjustment problem, as well as many of its variants, may be found, for example, in Blumen (1972), Gill (1982), McWilliams (1985), and Flierl (1987). Subsequent studies have continued to relate the basic principles to a range of oceanographic phenomena, including the adjustment of density fronts and their associated meanders (e.g., Ou 1984;van Heijst 1985;Garvine 1987;Spall 1995;Blumen and Wu 1995), the ocean response to storms (e.g., Geisler 1970;Price 1981), the dynamics of dense water outflows (e.g., Price and O'Neil Baringer 1994;Cenedese et al 2004), and ocean convection (e.g., Killworth 1979;Hermann and Owens 1993;Whitehead et al 1996;Rubino et al 2007), to name a few.…”
Section: A Motivation and Backgroundmentioning
confidence: 99%
“…Relevant to the present study, Saunders (1973) as well as Rubino and Brandt (2003) conducted experiments to test the simplest form of geostrophic adjustment in which they removed a thin-walled cylinder that separated higher and lower density fluids in a rotating cylindrical tank. Relevant to the present study, Saunders (1973) as well as Rubino and Brandt (2003) conducted experiments to test the simplest form of geostrophic adjustment in which they removed a thin-walled cylinder that separated higher and lower density fluids in a rotating cylindrical tank.…”
Section: A Motivation and Backgroundmentioning
confidence: 99%